A MODEL OFFICE APPROACH FOR CONFIGURING REUSABLE SOLUTIONS IN HEALTH IT - Subash Lekshmi Velayudhan, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article introduces a Model Office methodology for healthcare IT systems configuration, focusing on creating reusable and standardized implementations across various platforms. The approach addresses the challenges faced by healthcare payers in modernizing their legacy systems while maintaining operational continuity and regulatory compliance. Through structured implementation phases and standardized components, the methodology demonstrates significant improvements in configuration efficiency, error reduction, and cost savings across Commercial, Medicare, and Medicaid lines of business. The framework's adaptability and comprehensive testing protocols ensure consistent quality while enabling rapid deployment across different healthcare IT platforms, particularly in HealthRules Payor and Oracle Health Insurance (OHI) implementations.